PROBLEMS AND PERSPECTIVES IN EXTENDING POTATO CULTIVATION TO NONTRADITIONAL AREAS - Vanangamudi, K; Umarani, R.; Ravichandran, G.; Joseph, T. A.; Manorama, K. (Potato Journal, 2013)
In last five decades, the concentration of potato production is shifting from developed countries to developing countries. China and India ranked first and third largest potato producing countries, respectively in the world. The developing countries are expanding potato production for several reasons. Firstly, potato crop produces more edible energy and protein per unit time and area compared to cereal crops. Secondly, for the small subsistence farmers, potato fits well into multiple cropping systems prevalent in tropical and sub-tropical agro climatic conditions. Thirdly, the high profitability of potato cultivation, lastly, rapid technological advances, especially improved varieties agro techniques, irrigation etc. have stimulated expansion of potato production to non traditional environments.